(3JgPjH GdceGd aj CSeGA GdQLGds - (3jhSa Hf YHO GdQMef Hf jhSa, CHh GdMLGL, LeGd GdOjf GHf GdRcj CHj eMeO GdbVGYj GdcdHj GdeRj , J (B742 (3g` s
(3ChdgG (B:s
(3HbjI JQLeI YHjO Gddg Hf YHOGdcQje s
(3BNQgG (B:s
(3JQLeI YeQ Hf MHjH Gdeci s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B34s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B120 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdTjN eMeO fUja HLOg s
Keywords: (3GdJGQjNs